PERLINDUNGAN HUKUM INVESTOR DALAM KONTRAK PENGELOLAAN DANA KAITANNYA MANAJER INVESTASI MELANGGAR KETENTUAN POJK NOMOR 43/POJK.04/2015 TERKAIT BENTURAN KEPENTINGAN - Ajeng Kirana Miftakhul Jannah; Yudho Taruno Muryanto (Fakultas Hukum Universitas Sebelas Maret, 2024)
This article describes and examines the problem of first the conflict which is the position of investor in Discretionary Fund based on POJK Number 43 / POJK.04 / 2015. Second, the form of investors legal protection in the Discretionary Fund in relation to the Investment Manager violates the provisions of POJK Number 43 / POJK.04 / 2015 regarding conflicts of interest. This article is normative legal research with prescriptive nature. Data source in this research is including primary legal materials and secondary legal materials. The data collection technique is using literature study and the technical analysis is using deductive method. The result shows that according to POJK Number 43 / POJK.04 / 2015 investors in Discretionary Fund are given rights for their interests to take precedence over those of the Investment Manager.Then in Discretionary Fund in relation to the Investment Manager violates the provisions of POJK Number 43 / POJK.04 / 2015 regarding conflicts of interest, investors get legal protection both preventively and repressively which is accomodated in Undang-Undang Number 21 tahun 2011 about Otoritas Jasa Keuangan and Peraturan Otoritas Jasa Keuangan Number 43/POJK.04/2015.Keywords: conflict of interest; discretionary fund; legal protection